2010
DOI: 10.1039/c0cc00110d
|View full text |Cite
|
Sign up to set email alerts
|

A novel chiral oxazolidine organocatalyst for the synthesis of an oseltamivir intermediate using a highly enantioselective Diels–Alder reaction of 1,2-dihydropyridine

Abstract: Enantioselective Diels-Alder reactions of 1,2-dihydropyridines with acroleins using a novel chiral oxazolidine organocatalyst afforded chiral isoquinuclidines that is an efficient synthetic intermediate of oseltamivir, with fairly good chemical yield and excellent enantioselectivity (90%, up to >99% ee).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(31 citation statements)
references
References 11 publications
0
31
0
Order By: Relevance
“…60 It has been indicated that ibogaine reduces cravings for alcohol and other drugs by means of its ability to boost the levels of a growth factor known as glial cell lineÀderived neurotrophic factor. 62 We have already seen that Sialic acids are closely related to carboxylated sugars widespread in mammalian glycoproteins and glycolipids. Furthermore, isoquinuclidines are also valuable intermediates in the synthesis of other alkaloids and in medicinal chemistry.…”
Section: Dielsàalder and Hetero Dielsàalder Reactions And The Antiviralsmentioning
confidence: 99%
“…60 It has been indicated that ibogaine reduces cravings for alcohol and other drugs by means of its ability to boost the levels of a growth factor known as glial cell lineÀderived neurotrophic factor. 62 We have already seen that Sialic acids are closely related to carboxylated sugars widespread in mammalian glycoproteins and glycolipids. Furthermore, isoquinuclidines are also valuable intermediates in the synthesis of other alkaloids and in medicinal chemistry.…”
Section: Dielsàalder and Hetero Dielsàalder Reactions And The Antiviralsmentioning
confidence: 99%
“…47,48 Oxazoline derived from 1, linked at the terminal position of a substituted conjugated tetraene-1-carboxylic acid, acts as an effective chiral auxiliary in the 8π, 6π tandem electrocyclization affording bicyclo[6.2.0]octadiene products, dr 3:1. 49 Asymmetric Aldol and Henry Reactions.…”
Section: Rcho + Phmentioning
confidence: 99%
“…The oxazolidine ring system is found in different natural products as the central active site [16][17][18]. It has been reported that in some cases oxazolidine derivatives act as catalysts [19]. Compounds containing oxazolidine moieties found important applications as plasticizers, biocides [20][21][22][23], and pesticides [24,25].…”
Section: Introductionmentioning
confidence: 99%